Orientações pediátricas recebidas por pais de lactentes sobre hábitos de sono seguro e medidas de prevenção da síndrome de morte súbita - Souza, Janaina Samantha Martins de (2020)
Introduction: Sudden Infant Death Syndrome (SIDS) is defined as the sudden death of a child under one year of age without explanation, even after careful investigation including a complete autopsy, an examination of the death scenario and a review of the clinical history. Although the etiology is not defined, the risk factors, which are divided into extrinsic and intrinsic, are already well known and can be used as preventive measures. Objective: To verify if parents of children aged 0-12 months receive guidelines on safe sleep habits and measures to prevent sudden infant death syndrome in child care health consultations. Methodology: This is an exploratory, cross-sectional population-based study, which was carried out through a digital platform online using the Qualtrics® Software, having as subjects parents of infants aged 0-12 months that were born in all regions of Brazil. The instrument used was composed of 60 questions divided into groups. It started by 12 related to the socioeconomic profile and family structure, 18 were about the infant's current and perinatal health data, followed by 30 about sleeping habits and knowledge of SMSL and the campaign “Back to Sleep”. The questionnaire remained available from April 28, 2019 to May 18, 2020. Results: 642 parents of children between 0 and 12 months of age participated, being 47.0% aged between 24 and 33. Regarding sleeping habits, parents reported that 54.2% put their child to sleep in a crib next to their bed and 16.6% indicated bed-sharing. The position most chosen for the baby to sleep is on supine, as informed by 50.6% of parents, but 44.3% still use lateral sleep, as they feel safer. Regarding smoking habits, only 12 (1.8%) infants were exposed to tobacco during the whole pregnancy and 10 (1.5%) mothers smoked at the beginning, whereas 617 (96.1)% did not smoke. Around a third of the babies received exclusive breastfeeding and 12.7% were breastfed up to six months. Most parents (74.1%) mentioned having received the correct guidance about the proper sleeping position (supine position), being 45.6% given by the doctor/pediatrician and 12.7% by the nurse. Therefore, the supine position for sleeping was the most recommended by pediatricians. When asked if they had heard of the “Back to Sleep” campaign, 47.3% reported that they did not know, while 279 (43.4%) said they did. Regarding the question whether they believed putting the baby to sleep on position supine could save their lives, 273 (62.2%) said they did, but we still have an important number of 121 (27.6%) parents who said they had no knowledge of it. There was a significant difference in the regions in relation to age (p = 0.014), race (p <0.001), education (p = 0.001) and income (p <0.001). Regarding age, in all regions the age of 24 to 33 prevailed, however, in the west respondents were significantly younger and in the south, older. With regard to race, Caucasians were predominant in the states of the south, southeast and northeast, while mixed were in the Midwest and north. As for the level of education, most respondents had concluded high school or graduated, however, there was a significant difference between the south and the southeast, where the respondents reported higher / lower levels. Regarding income, most respondents are in the range of 3 to 15 national minimum wages. Wages were significantly higher in the south and lower in the Midwest. Significant differences were observed between the regions considering the place of prenatal care (p <0.001), type of delivery (p <0.001) and primary child care health consultations (p <0.001). There is a predominance of prenatal consultations in private health care in the south, and in public health care in the north. There is a predominance of vaginal deliveries in the southeast, northeast and north regions, whist the elective cesarean section stood out in the south, northeast and Midwest and mandatory cesarean section prevailed in the states of the south, Midwest and north. With regard to child care health consultations at the Basic Health Unit (SUS), it prevailed only in the north, while in other regions most consultations happened in a private office. As for the sleep habits according to geographic regions, we observed there is a significant difference in the regions considering the position normally used to sleep (p <0.001) and regarding the delivery of guidelines from pediatric/primary care physicians (p = 0.029). The supine position was the mostly indicated in the south, Midwest and north regions. Pediatric/primary care doctors advised more frequently on the sleeping position in the south, southeast and Midwest regions. Conclusion and final considerations: The correct guidance of the pediatrician concerning sleeping positions reflects in safe sleep practices and greater knowledge of SIDS. It is noteworthy that some parents continue to adopt risky behaviors despite having received the correct guidelines. It is still necessary to resume campaigns to deepen the knowledge about SIDS and to raise awareness among parents, grandparents, caregivers and health professionals about the need to comply with the recommendations for SIDS prevention, being that the only way to prevent the death of infants.